A Phenomenological Study: Tourism Students’ Views on Hotel Internship Experiences in Indonesia - Yulia Kurnia Sari Sitepu; Wolter Parlindungan Silalahi; Merry Silalahi; Hanna Manurung; Karteria Lumbantobing (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study explored the lived experiences of tourism students interning in a hotel in Indonesia. Using a qualitative research design, the data was collected from four tourism students enrolled in undergraduate degree program at a public college in northern Indonesia using semi structured interviews. The study findings showed that students acquire new knowledge and have a good day off during their internship. During their internship, they gained new knowledge, such as collaboration effort, time management, hospitality, cleanliness and order. In the collaboration effort, students can design a better learning environment, and the collaboration among supervisors raises students' achievement. In addition to receiving access to templates they may use immediately to write their reports and submit them to their college advisor, they would learn what a weekly report was, how to construct one, and other related information. Additionally, this study would be helpful for their juniors who will conduct internships in the future. Future studies might enhance the comprehension of how interns socialize and how it relates to their learning, performance, and fulfilling experiences during internships.